DISABLING WORK: NEOLIBERAL LABOR, DIGITAL GOVERNANCE, AND THE MAKING OF STRUCTURAL IMPAIRMENT IN INDONESIA’S SERVICE INDUSTRIES - Khalid Syaifullah,; Wardatul Adawiah, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
Occupational disability is often defined in terms of physical impairment or social exclusion. However, in neoliberal service economies like Indonesia, disablement increasingly emerges from everyday labor conditions. This study explores how digital governance, algorithmic control, and performance pressure contribute to structural disablement among service workers. Based on qualitative fieldwork from January to March 2025 in Jakarta, West Java, and Banten, we conducted in-depth interviews and participant observation across transportation, graphic design, civil service, and education sectors. Using a grounded political economy approach and Engels’ concept of social murder, we argue that disablement is produced within the labor process itself. Workers reported chronic pain, anxiety, insomnia, and emotional exhaustion linked to blurred work-life boundaries and digital surveillance. Despite these harms, managerial narratives normalize suffering under the guise of productivity and resilience. Occupational health programs fail to recognize cumulative, non-visible harm, especially in the Global South. Many workers did not identify as disabled despite ongoing impairment. We reconceptualize disability as a structural outcome of labor regimes, urging systemic reform beyond individualized care.